Tiêu thụ điện năng, đầu tư trực tiếp nước ngoài và tăng trưởng kinh tế Việt Nam: Phương pháp ARDL - Đinh Thị Thu, Hồng; Huỳnh Thái, Huy; Lê Thị Kim, Loan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
International experience in economic development industrialization has revealed the increasing importance of energy factors. The objective of this paper is to investigate the causality among electricity consumption, foreign direct investment, and economic growth in Vietnam for the period of 1986-2014, by using Toda-Yamamoto approach and autoregressive distributed lag (ARDL) approach. The empirical results show that electricity consumption and foreign direct investment have a long-run positive effect on economic growth. This paper shows that there exist unidirectional causality running from foreign direct investment to economic growth and bidirectional causality between economic growth and electricity consumption, which supports the feedback hypothesis
Keywords: Electricity consumption; Economic growth; ARDL; Toda-Yamamoto